Barriers to Organizational Change Management in Hotel Industry of Nepal - Chalise, Dhan Raj (Nepal Journal of Multidisciplinary Research, 2021)
In initial period, organizational changes are asks for entire hospitality industry. Thus, this research paper reveals what are the barriers for organizational change management in hotel sectors of Nepal which can help them for gaining spark on Nepalese market once again.: Hotels sectors of Nepal are affected by array of factors which can influence organizational performance. This is the component of success for enhancement of performance of hotel sector. Therefore, the purpose of this research is to examine the factors influencing organizational performance in hotel sector of Nepal. This research is based on hotel sector’s organizational changes and the barriers for adaptation of such changes. The study of hotel sector is done with self-structured questionnaire and mostly data are collected from primary sources. To justify the results, researcher has adopted quantitative research design and SPSS software is used for data analysis. The research has identified the essence of organizational changes in hotel sector. In the time of financial plummeted of Nepalese economy, hospitality sector are hardly hit by global pandemic. Thus, hotel sector need new plan and strategies for achieving success. Through organizational changes, hotel sector can slowly and steadily moves business in path of positives. So, hotel sector has to identify barriers of organizational change management and has to act accordingly to achieve success in this critical hour. Nepalese economy after hard hit by global pandemic has slowly started to move in towards path of recovery. To step up Nepalese economy in decent path every sector need to contribute. Hotel sector being the important hub of national GDP has to recover from crises for development of country. Therefore, hotel sector with organizational change management can enhance their profitability. This research in this regard is helpful for Nepalese hotel sector to identify and adopt such changes. This research paper is the summarization of results carried on primary data collected from questionnaire. The research is done on data collected from field so is highly reliable.